Nová a zlepšená kardiopulmonální resuscitace - Garza, Alex G (Clinical Cardiology Alert, 2009)
Cardiac arrest continues to have poor survival in the United States. Recent studies have questioned current practice in resuscitation. Our emergency medical services system made significant changes to the adult cardiac arrest resuscitation protocol, including minimizing chest compression interruptions, increasing the ratio of compressions to ventilation, deemphasizing or delaying intubation, and advocating chest compressions before initial countershock. METHODS AND RESULTS: This retrospective observational cohort study reviewed all adult primary ventricular fibrillation and pulseless ventricular tachycardia cardiac arrests 36 months before and 12 months after the protocol change. Primary outcome was survival to discharge; secondary outcomes were return of spontaneous circulation and cerebral performance category. Survival of out-of-hospital arrest of presumed primary cardiac origin improved from 7.5% (82 of 1097) in the historical cohort to 13.9% (47 of 339) in the revised protocol cohort (odds ratio, 1.80; 95% confidence interval, 1.19 to 2.70). Similar increases in return of spontaneous circulation were achieved for the subset of witnessed cardiac arrest patients with initial rhythm of ventricular fibrillation from 37.8% (54 of 143) to 59.6% (34 of 57) (odds ratio, 2.44; 95% confidence interval, 1.24 to 4.80). Survival to hospital discharge also improved from an unadjusted survival rate of 22.4% (32 of 143) to 43.9% (25 of 57) (odds ratio, 2.71; 95% confidence interval, 1.34 to 1.59) with the protocol. Of the 25 survivors, 88% (n=22) had favorable cerebral performance categories on discharge. CONCLUSIONS: The changes to our prehospital protocol for adult cardiac arrest that optimized chest compressions and reduced disruptions increased the return of spontaneous circulation and survival to discharge in our patient population. These changes should be further evaluated for improving survival of out-of-hospital cardiac arrest patients.
Keywords: urgentní zdravotnické služby; American Heart Association; Spojené státy americké; Humans; elektrická defibrilace; lidé středního věku; oxygenoterapie; analýza přežití; Cardiopulmonary Resuscitation; masáž srdce; Female; Aged; Kansas; dospělí; srdeční zástava; výsledek terapie; senioři; lidé; kardiopulmonální resuscitace; Heart Massage; Electric Countershock; United States; Survival Analysis; fibrilace komor; časové faktory; intratracheální intubace; Intubation, Intratracheal; Adult; Oxygen Inhalation Therapy; klinické protokoly; Americká kardiologická asociace; Practice Guidelines as Topic; ženské pohlaví; Insufflation; Brain Damage, Chronic; Male; Middle Aged; Retrospective Studies; Treatment Outcome; směrnice pro lékařskou praxi jako téma; Ventricular Fibrillation; insuflace; chronické poškození mozku; retrospektivní studie; Clinical Protocols; Heart Arrest; mužské pohlaví; Time Factors; Emergency Medical Services